The Association Among Achievement Goal Orientations, Academic Performance, and Academic Well-Being Among Chinese Medical Students: A Cross-Sectional Study - Li, Qing-lin; Zhao, Ji-yang; Tian, Jing; Sun, Tao; Zhao, Chen-xi; Guo, Hai-chen; Zhu, Li-yan; Gao, Rui; Yang, Li-bin; Cao, De-pin; Zhang, Shu-e (Frontiers in Psychology, 2021)
Abstract Learning motivation is a significant factor that ensures quality in medical education, and might affect the academic performance and well-being of medical students. This study aimed to explore the status of achievement goal orientations among medical students in China and to further identify the association among academic performance, academic well-being, and achievement goal orientations. Data were collected through a cross-sectional, anonymous survey conducted with 3,511 respondents (effective response rate = 81.7%), from four medical universities in China, and demographic factors, achievement goal orientations, academic performance, and academic well-being were assessed. The average score of achievement goal orientations of Chinese medical students suggested a difference in demographic factors, including sex, year of study, experience of leadership cadre, and family income. Both mastery and performance-avoidance goals were associated with academic performance, subjective academic stress, subjective learning adaptability, subjective sleep quality, and subjective well-being. Performance-approach goals were related to academic performance, subjective academic stress, and subjective learning adaptability. The achievement goal orientations of the medical students in this study were at a middle level. The findings emphasize the importance of mastery goals for promoting the academic performance and well-being of medical students. More care and attention toward achievement goal orientations can be beneficial for the improvement of the academic performance and well-being among medical students.